High Prevalence Of Low Back Pain Among Medical Students In Malaysia – A Concern For Intervention - Muhammad Asyraaf Amir Husin; Mohd Zarawi Mat Nor; Nizam Baharom; Mohd Radzniwan A Rashid; Nadeeya'ayn Umaisara Mohamad Nor; Faizul Helmi Addnan; Anuar Sani (USM, 2024)
Vol.6, No.1, December 2021, pp. 86–92